Capital Flows and Economic Growth in Ghana. Issue 3 (1st September 2016) - Klobodu, Edem Kwame Mensah; Adams, Samuel
ABSTRACT: The study examines the differential effects of capital flows on economic growth in Ghana over the period 1970–2014 using autoregressive distributed lag (ARDL). Breakpoint unit root tests are employed to cater for structural change and breaks in time series. Afterwards, these break dates are fed into the ADRL model as dummy variables to allow for the computation of a more robust cointegrating vector. The findings indicate that in both the short and long run capital flows (i.e. FDI, aid, and external debt) have negative effects on economic growth. However, remittances exhibit positive insignificant elasticity in all the regressions. Further, the empirical results show that while the impact of trade, gross capital formation and population growth on growth are mixed, that of inflation is negative. The results of the study are consistent with the idea that the impact of capital flows in Africa has been exaggerated.